Impact of Chemical Environment on Compaction Creep of Quartz Sand and Possible Geomechanical Applications. Issue 6 (23rd June 2019) - Schimmel, M. T. W.; Hangx, S. J. T.; Spiers, C. J.
Abstract: Induced seismicity and surface subsidence are adverse effects of natural gas and geothermal energy production that may present barriers to their use as low‐carbon alternatives to coal and oil. The driving force for these unwanted effects is compaction of the reservoir, which can potentially be mitigated by injecting (pressurized) fluids that restore the pore pressure and chemically inhibit compaction. We conducted uniaxial compaction experiments on quartz sand aggregates to investigate the effect of pore fluid chemistry on time‐dependent compaction (creep). In addition to a low‐vacuum (dry) environment, supercritical fluids (N2, CO2, and wet CO2 ), simple aqueous solutions (three HCl solutions and a NaOH solution), and complex aqueous solutions with additives (AlCl3, AMP, and washing detergent) were employed. N2, CO2, and fluids containing scaling inhibitor (AMP), as well as wastewater (detergent solution) are generally considered for injection. Compaction creep was enhanced in fluid‐saturated environments compared to dry. Wet CO2 caused more creep with faster strain rates than the relatively dry CO2 and N2 environments. Experiments conducted with simple aqueous solutions exhibited a clear pH dependency. The complex aqueous solutions enhanced creep compared to their simple solution counterpart with similar pH. Based on acoustic emission data and microstructural analyses, we inferred that compaction creep was controlled by subcritical crack growth, aided by water, hydroxyl ions, and additives. If microcracking also controls compaction in reservoir sandstones, these results indicate that injection of supercritical fluids or acidic solutions may mitigate reservoir compaction. Key Points: Creep of quartz sand by subcritical cracking is strongly impacted by pore fluid chemistry Low water content and low fluid pH inhibit crack tip bond hydrolysis and hence creep Injected fluid chemistry may influence reservoir compaction and induced seismicity